2020
DOI: 10.1109/access.2020.3003619
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Fractional-Order Embedding Geometrical Multi-View CCA (SFGMCCA) for Multiple Feature Integration

Abstract: Techniques for integrating different types of multiple features effectively have been actively studied in recent years. Multiset canonical correlation analysis (MCCA), which maximizes the sum of pairwise correlations of interview (i.e., between different features), is one of the powerful methods for integrating different types of multiple features, and various MCCA-based methods have been proposed. This work focuses on a supervised MCCA variant in order to construct a novel effective feature integration framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As a solution to this problem, multivariate analysis models that introduce label dequantization have been proposed [ 48 , 49 ], and their use will be considered in future work. In addition, while general CCA is based on two types of data, methods based on multi-view CCA are effective when various types of data are used [ 50 , 51 ], as in our experiment in this paper. Capturing more complex correlations will become feasible by introducing the above methods.…”
Section: Resultsmentioning
confidence: 99%
“…As a solution to this problem, multivariate analysis models that introduce label dequantization have been proposed [ 48 , 49 ], and their use will be considered in future work. In addition, while general CCA is based on two types of data, methods based on multi-view CCA are effective when various types of data are used [ 50 , 51 ], as in our experiment in this paper. Capturing more complex correlations will become feasible by introducing the above methods.…”
Section: Resultsmentioning
confidence: 99%
“…(1), we obtain the general eigenvalue problem of Eq. (7) [32], [33]. BiTl-dMCCA is an extended version of dMCCA that solves the problem.…”
Section: B Bidirectional Time Lag Aware Deep Multiset Canonical Correlation Analysismentioning
confidence: 99%
“…CCA can represent a lower-dimensional common latent space in This work was partly supported by the MIC/SCOPE #181601001. such a way that a pair correlation of the multi-view data is maximized. In particular, CCA which can be applied to three or more kinds of modalities is called multi-view CCA (MVCCA) [5][6][7][8]. Furthermore, to realize more accurate representation of the lowerdimensional common latent space, some advanced MVCCA-based approaches have been studied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a method utilizing label information based on mG-PLVM has been proposed [15], and this method considers intra-and inter-class correlations in the same manner as linear discriminant analysis (LDA) [16]. Incidentally, a recent study [8] have revealed that the direct use of label information as one modality can estimate the more effective common latent space than correlation coefficientbased approaches. Thus, by introducing label information as one of the modalities into mGPLVM, it is expected that better representation of the common latent space can be obtained.…”
Section: Introductionmentioning
confidence: 99%